Analysis of Internal Control System Accounts In SME & SR Partnership Program Pertamina - Busnia, Yahdi Furqon; Widijoko, Grace (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
The objective of this research is to determine and evaluate the internal control system of the accounts receivables at Program Kemitraan dan Bina Lingkungan (PKBL) PT. Pertamina (Persero). This research used qualitative descriptive method with a case study approach. The data in this research is obtained through observation, interviews, and documentation. The result of this research shows that the system of internal control over accounts receivables at Program Kemitraan dan Bina Lingkungan (PKBL) PT. Pertamina (Persero) already works quite effectively, where the management of company has implemented the basic concepts and principles of internal control by COSO, however still needs some improvement. Improvements need to be made on the company's policy against the policy of the Standard Operating Procedure (SOP) applicable so that no misappropriation of funds outside loans. for Partners (PTPN) to reinforce regulations enacted and payment for farmers who are given loans so that no late payment when it is due and for Farmers that comply with regulations as well as the payment of the loan application that uses collateral to anticipate risks. Keywords: Internal Control Systems, Accounts Receivables, COSO